Gravity, Cosmology, and Astrophysics A Journey of Exploration and Discovery with Female Pioneers - Hartmann, Betti; Kunz, Jutta; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This open access book is a compilation of enlightening tutorial essays, showcasing the forefront of research by exceptional female scientists. This invaluable collection provides graduate students and researchers in the field with an engaging and pedagogical introduction to a wide range of compelling topics. Delve into the depths of theoretical and observational realms, exploring intriguing subjects including modified gravity models, quantum gravity, fields in curved space-time, particle dynamics, gravitational waves, and enigmatic black holes. Embracing both the theoretical foundations and the practical applications, this comprehensive edited volume offers an accessible and all-encompassing panorama of gravity and cosmology. Moreover, it shines a much-needed spotlight on the significant contributions made by remarkable women across the globe, fostering recognition and admiration for their indispensable role in shaping this ever-evolving field. This book is licensed under the terms of the Creative Commons Attribution-NonCommercial 4.0 International License (http://creativecommons.org/licenses/by-nc/4.0/). For further details see license information in the chapter.
Part I. Astrophysics & Observations -- Chapter 1. Quasinormal Modes of Static Ellis-Bronnikov Wormholes (Bahareh Azad) -- Chapter 2. Stationary models of relativistic viscous torus (Sayantani Lahiri) -- Chapter 3. Shadows and accretion disk images of compact objects (Petya Nedkova) -- Chapter 4. The optical appearance of compact stars: Shadows and luminous rings (Merce Guerrero) -- Chapter 5. Beyond Newtonian Dynamics of Planar CRTBP with Kerr - like Primaries (Suparna Roychowdhury) -- Part II. Extended gravity models -- Chapter 6. Neutron Stars in General Relativity and in Alternative Gravity Theories: Quasinormal Modes and Universal Relations (Fech Scen Khoo) -- Chapter 7. Introduction to stellar and substellar physics in modified gravity (Aneta Wojnar) -- Part III. Cosmology -- Chapter 8. Chameleon perfect scalar field as a geometric correction in f (R) gravity (Laura L. Parrilla) -- Chapter 9. Probing the nature of cosmic strings with gravitational waves (Lara Sousa) -- Part IV. Quantum Gravity & Mathematical Relativity -- Chapter 10. Entanglement in conformal field theory and holography (Nele Callebaut) -- Chapter 11. Coordinates are messy $1 (Bnot only in General Relativity (Carla Cederbaum) -- Chapter 12. Primordial Black Holes and Higgs Vacuum Decay (Ruth Gregoryz).s
Keywords: Gravitation; Cosmology; Elementary particles (Physics).; Quantum field theory; Mathematical physics; Astrophysics; Classical and Quantum Gravity; Cosmology; Elementary Particles, Quantum Field Theory; Theoretical, Mathematical and Computational Physics; Astrophysics